Physiology and production of sesame genotypes BRS-Seda and Preto under organomineral fertilization - Saint-Clear S. e Santos; Pedro D. Fernandes; Messias F. de Queiroz; Nair H. C. Arriel; Victor H. de A. Ribeiro; Josely D. Fernandes (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT Sesame is an oilseed that has low demand of water; it is widely grown in tropical regions, but few studies had been conducted on its mineral nutrition. The objective of this study was to evaluate physiological and production variables of two sesame genotypes (BRS-Seda and Preto) varying the organomineral fertilizer doses, via fertigation. The genotypes were grown under field conditions during the 2014/2015 dry season, in an agricultural area in Lagoa Seca, PB, Brazil. The two genotypes were subjected to five doses (0, 30, 60, 90 and 120% of the nutritional requirement of the crop) of an organomineral fertilizer based on sugarcane vinasse, and to an additional treatment consisting of mineral fertilizer (100% of the crop requirement). The experiment was conducted in a randomized block design, in a (2 x 5 + 2) factorial arrangement, with 12 treatments and 4 repetitions, totaling 48 plots. Among the physiological variables evaluated, only internal CO2 concentration was affected by the organomineral fertilizer doses. The number of fruits per plant, fruit weight per plant, seed weight per plant, and 1000 seed weight of both cultivars were favored by the organomineral fertilization. The organomineral fertilizer dose of 120% provided better results for the two sesame genotypes than those found with the mineral fertilization.